MODEL PEMBELAJARAN BERBASIS PROYEK DENGAN PENDEKATAN GRASPS PADA MATA KULIAH TEKNIK PEMROGRAMAN - Tati Mardiana (Cakrawala - Jurnal Humaniora, 2012)
There are many of Information Technology students who have graduated but are still unemployeed. It may be caused by the lackness of students who are still unable to develop their skills to what their needs. university needs to do a review of the learning method applied in the classroom by the lecturer. It is important to choose the suitable learning method to achieve optimal learning outcomes. This research is aimed to give a hint of a design to a learning method based on GRAPS (Goal, Role, Audience, Situation, Products, Standards) to improve the result of learning and student’s thinking skills on Programming Technique subject. This is a qualitative research whose data is collected  by observing to progamming techniques subject during learning process, interviewing some respondents, and doing a library research to some related literature books and journals. The results of learning by using this kind of method, in which GRAPS method, is better than the old conventional learning method. This kind of method  are able to improve the outcomes of student’s ability and student’s thinking skills to Programming Technique subject. Keywords : learning, project, GRAPS, learning outcomes, programming technique subject.